Single Nucleotide Polymorphims (snps) Identification of Inhibin Sub Unit-α (inha) Gene on Madura Bulls - Irida Novianti; Chairdin Dwi Nugraha; Rafika Febriani Putri; Ahmad Furqon; Wike Andre Septian; S. Rahayu; V. M. A. Nurgiartiningsih; Suyadi Suyadi (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2021)
INHA gene is a gene that is suggested to have role in reproductive system. Single Nucleotide Polymorphisms (SNPs) of Madura Bulls were identified in this study. Polymerase Chain Reactions (PCR) was used to amplify INHA gene region and MEGA 7 program was utilized to align the amplified region sequences with sequence from Ensembl database. Four SNPs found in INHA and they are located at the first exon. Two SNPs were misssense mutations that causing the substitution of amino acid leucine21 by proline, and amino acid valine63 by methionine and the other two SNPs were synonymous mutation. One of the synonymous SNPs was a novel mutation. Based on those identified SNPs, they could be suggested as potential candidate markers of reproduction traits for Madura bulls. Moreover, through heterozygosity value from the observed bulls, it was indicated that the genotype was varied in population. Therefore a molecular selection program could be designed to determine the Madura superior bull.